2012
DOI: 10.1016/j.imbio.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mice expressing human CR1/CD35 have an enhanced humoral immune response to T-dependent antigens but fail to correct the effect of premature human CR2 expression

Abstract: We have previously demonstrated that mice expressing human complement receptor type 2 (CR2/ CD21) during the CD43 + /CD25 -late pro-B cell stage of B cell development have marked changes in their subsequent B cell ontogeny. Here, we show that the humoral immune response to the T cell dependent antigen, sheep red blood cells (SRBC) can be moderately enhanced with the addition of human CR1 (driven by the lambda promoter/enhancer transgene) to endogenous mCR1/CR2 expression on the B cell surface but that hCR1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…hCR1 tg .hCR2 tg . Cr2 −/− mice ( Pappworth et al, 2012 ) and hCR2 tg .C3 −/− mice ( Twohig et al, 2007 ) were routinely confirmed by PCR and immunoblot. All mice used were age and sex matched littermates from colonies maintained at Newcastle University or purchased (B6) from Harlan (UK).…”
Section: Methodsmentioning
confidence: 99%
“…hCR1 tg .hCR2 tg . Cr2 −/− mice ( Pappworth et al, 2012 ) and hCR2 tg .C3 −/− mice ( Twohig et al, 2007 ) were routinely confirmed by PCR and immunoblot. All mice used were age and sex matched littermates from colonies maintained at Newcastle University or purchased (B6) from Harlan (UK).…”
Section: Methodsmentioning
confidence: 99%
“…These studies have not delineated the specific functions of the Cr1 and Cr2 proteins on B cells and FDC, and elevated surface expression of CD19 on Cr1/2KO B cells has been proposed to lead to B cell anergy (17). Additional studies have also utilized Cr1/2 deficient ( Cr1/2KO ) animals to examine the function of human CR1 or CR2 via transgenic expression models of these proteins using immunoglobulin gene promoters (18, 19). In these studies, however, premature expression of the transgenes (compared to native Cr2 ), lack of FDC expression, expression in inappropriate cell types (T cells, etc), and the structural distinctness of human CR1 compared to the mouse Cr1 protein introduces critical variables.…”
Section: Introductionmentioning
confidence: 99%
“…A similar goal was advanced recently by the creation of a transgenic Cr1/2KO mouse line expressing human CR1/CD35 (Pappworth et al, 2011). However, in addition to the expression of human CR1 in a non-autochthonous environment these mice possess other disadvantages including premature expression of CR1 during B cell development, a broader cell specific expression pattern than murine Cr1, and the absence of the CD19 co-association exhibited by mouse Cr1.…”
Section: Discussionmentioning
confidence: 99%